2012
DOI: 10.1177/1087054711434155
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits in Adults With ADHD Go Beyond Comorbidity Effects

Abstract: Neuropsychological deficits in adults with ADHD go beyond comorbidity. Specific comorbid disorders may influence the neuropsychological functioning in adults with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
2
15
1
Order By: Relevance
“…We previously reported that BD and ADHD had significant and independent effects on Stroop color test measures of the executive function inhibitory control domain (14). The present findings suggest that WCST score deficits may be largely associated with BD rather than ADHD.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…We previously reported that BD and ADHD had significant and independent effects on Stroop color test measures of the executive function inhibitory control domain (14). The present findings suggest that WCST score deficits may be largely associated with BD rather than ADHD.…”
Section: Discussionsupporting
confidence: 53%
“…A review of studies on this topic pointed to similarities between BD and ADHD in their neuropsychological function (30). More specifically, mania and ADHD might share deficits in vigilance regulation (31) and sustained attention (14,32). By contrast, subtle differences in various areas of executive function emerge as specific to each disorder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, ADHD patients with a comorbid psychiatric disorder showed greater neuropsychological deficits than ADHD patients without comorbidity (Hervey et al, 2004) and may represent a distinct subgroup, with different cognitive profiles (Fischer et al, 2007). However, it has also been shown that cognitive deficits in adult ADHD cannot be accounted for by comorbid disorders (Nigg et al, 2005a; Silva et al, 2013). Major depressive disorder (MDD) is the most frequently observed comorbidity, and can co-occur with ADHD in up to 50% of the cases (Wilens et al, 2009).…”
Section: Introductionmentioning
confidence: 99%